19.1k views
2 votes
If f(x) = 2x - 1 and g(x) = 2x + 1, evaluate f(g(x)) when x = -3

User Rlafuente
by
5.8k points

1 Answer

4 votes

Answer:

f(g(-3)) = -11

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Functions
  • Function Notation
  • Composite Functions

Explanation:

Step 1: Define

Identify

f(x) = 2x - 1

g(x) = 2x + 1

x = -3

Step 2: Evaluate

  1. Substitute in x: f(g(-3))
  2. Substitute in x [Function g(x)]: g(-3) = 2(-3) + 1
  3. Multiply: g(-3) = -6 + 1
  4. Add: g(-3) = -5
  5. Rewrite: f(-5)
  6. Substitute in x [Function f(x)]: f(-5) = 2(-5) - 1
  7. Multiply: f(-5) = -10 - 1
  8. Subtract: f(-5) = -11
User Steve Goykovich
by
6.2k points